Design Research on Realistic Mathematics Education Using Sedekah Rame to Develop Students’ Number Sense - Anna Fauziah; Dona Ningrum Mawardi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
The dominance of procedural learning in mathematics highlights the need for contextual learning to develop students’ number sense. This study aims to develop a realistic mathematics education learning design based on the local cultural context of Sedekah Rame to enhance junior high school students’ number comprehension. This research employed a validation design research method through three stages: preliminary design, teaching experiments, and retrospective analysis. The participants were 8th-grade students of SMP Negeri 3 Lubuklinggau. Data were collected using observation sheets, student worksheets, interviews, field notes, and documentation. Qualitative data analysis was conducted through data reduction, data display, and conclusion drawing with triangulation to ensure validity. The learning design focused on four indicators of number sense: estimation, mental calculation, assessment of numerical magnitude, and assessment of result rationality. The findings show that the Sedekah Rame context provides meaningful mathematical situations and supports the emergence of flexible numerical strategies. However, the development of number comprehension requires strong conceptual understanding and continuous learning experiences. The findings indicate that the Sedekah Rame cultural context supports the development of students’ number sense by encouraging flexible numerical reasoning. However, strengthening conceptual understanding and providing continuous, well-structured learning experiences are essential to achieve more consistent improvement.